From child-peer similarity in imitative behavior to matched peer-mediated interventions in autism - Xavier, Jean; Johnson, Simona; Cohen, David (Frontiers in Psychology, 2023)
Self-consciousness develops through a long process, from pre-reflexive consciousness relying on body perception, to “meta” self-awareness. It emerges from the imitative experience between children and their peers. This experience linked to the capacity to test structural similarities between oneself and others, is addressed according to the concept of interpersonal affordance. We hypothesize that the opportunity for co-actors to engage in a process of interpersonal coordination is underlined by their similarity in terms of morphological, behavioral and motor features. This experience can sustain the emergence of new affordances for objects for each co-actor, as well as new affordances in terms of joint actions. We apply this idea in the context of peer-mediated interventions (PMI) in autism spectrum disorder (ASD). We argue that, in PMI, an encounter between children with autism and similar peers would foster the opportunity to engage in a spontaneous process of interpersonal coordination. This process would enable the development of self-consciousness and the emergence of perception of interpersonal, self and other’s affordances for children with autism. We conclude that metrics to assess morphological, behavioral and motor similarity should then be defined and used in future studies to test our hypothesis in children with autism versus TD children or between children with autism.